2017
DOI: 10.1021/acschemneuro.7b00090
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Realm of Allosteric Modulators for Opioid Receptors for Future Therapeutics

Abstract: Opioids, and more specifically μ-opioid receptor (MOR) agonists such as morphine, have long been clinically used as therapeutics for severe pain states but often come with serious side effects such as addiction and tolerance. Many studies have focused on bringing about analgesia from the MOR with attenuated side effects, but its underlying mechanism is not fully understood. Recently, focus has been geared toward the design and elucidation of the orthosteric site with ligands of various biological profiles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 111 publications
0
31
0
Order By: Relevance
“…For example, it is anticipated that positive allosteric modulators will enhance the activity of endogenous opioid peptides, maintain their temporal and spatial action, and potentially limit the off-target adverse effects. Although several such compounds have been characterized in vitro , their utility in vivo is yet to be determined ( Remesic et al, 2017 ).…”
Section: Other Approachesmentioning
confidence: 99%
“…For example, it is anticipated that positive allosteric modulators will enhance the activity of endogenous opioid peptides, maintain their temporal and spatial action, and potentially limit the off-target adverse effects. Although several such compounds have been characterized in vitro , their utility in vivo is yet to be determined ( Remesic et al, 2017 ).…”
Section: Other Approachesmentioning
confidence: 99%
“…Allosteric modulators of opioid receptors (Remesic et al, 2017) constitute another priority area of research with expected higher probability of success in the development of medications in response to the opioid crisis (Rasmussen et al, 2019). NIDA’s “most wanted” allosteric modulators of opioid receptors include MOP PAMs (Rasmussen et al, 2019).…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…One of the reasons why MOP PAMs are of potential interest is that by increasing the potency and/or efficacy of classical opioid drugs, they are expected to produce the same analgesic response achieved by higher doses of opioid drug while simultaneously presenting fewer on-target overdosing risks. Most importantly, these compounds may not be subject to the compensatory mechanisms deriving from chronic MOP activation (e.g., tolerance, dependence, and increased toxicity) because they preserve the temporal and spatial fidelity of signaling in vivo by acting only in the presence of endogenous or other orthosteric ligands (Remesic et al, 2017).…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…Different strategies have been developed in the search for safer opioid analgesics, including increasing endogenous opioid signaling with enkephalinase inhibitors [ 3 , 4 ] use of mu opioid receptor positive allosteric modulators [ 5 , 6 ] peripherally restricted opioids [ 7 ] or pH-dependent mu-receptor agonists [ 8 , 9 ] and mixed opioid receptor agonists [ 10 , 11 ]. In addition, mixed agonists for mu and nociceptin/orphanin FQ receptors, showing promising profiles in preclinical studies, have been recently reported in the literature (reviewed in [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%